Facing natural disasters through the endorsement of authoritarian attitudes. (April 2020) - Russo, Silvia; Mirisola, Alberto; Dallago, Francesca; Roccato, Michele
Abstract: We analyzed the relations between exposure to news describing a natural disaster and right-wing authoritarianism (RWA) with 241 Italian adults, surveyed twice, before and after a severe earthquake. Our results were compatible with the idea that the exposure to earthquake news led to an increase in RWA among people who had low, but not among who had relatively high, authoritarian levels before the event. We discuss the findings in terms of compensatory control, and highlight strengths and limitations of the study. Highlights: We examined right-wing authoritarianism (RWA) before and after an earthquake. RWA at T1 moderates the effect of exposure to news about the disaster on RWA at T2 . Exposure to news fosters RWA at T2 only among people with low RWA at T1 . Our findings show a previously unexplored consequence of natural disasters. The findings also uncovered a new link between threat and RWA.